PENGARUH INTENSITAS MENONTON LIVE STREAMING PENJUALAN (LAZLIVE) DI LAZADA DAN AKTIVITAS WORD OF MOUTH TERHADAP MINAT BELI DI LAZADA - Nur Fadila, Jihan; Lukmantoro, Triyono; Manalu, Rouli (Interaksi Online, 2024)
Competition between e-commerce makes each platform compete with each other's strategies. Not wanting to be less competitive with its competitors, Lazada created a sales feature via live streaming in 2019. This feature is called LazLive which is expected to be able to increase the number of sales or transactions at Lazada. In fact, the number of transactions and sales at Lazada is at the bottom compared to its competitors. Especially with the momentum of Harbolnas 12.12 2023, of course this momentum is an opportunity for business owners to maximize their sales. A person's desire to buy a product is influenced by assessments originating from word-of-mouth activities. The purpose of this research is to determine the influence of the intensity of watching live streaming sales (LazLive) on Lazada and word of mouth activity on buying interest on Lazada. The theories used in this research are Cognitive Response Theory and Traditional Word Of Mouth Communication Theory. This research used a sample of 60 people aged 18-55 years who had watched, heard, and carried out word of mouth activities both online and offline about LazLive and lived on the island of Java. The sampling technique for this research uses non-probability with a purposive sampling method approach. The research results show that there is a significant influence on the variable intensity of watching live streaming sales (LazLive) on Lazada (X1) on buying interest on Lazada (Y), a significance value of 0.001 is obtained, where this figure is smaller or less than (<) 0.05 with a regression coefficient of 0.098. Likewise, for the word of mouth activity variable (X2) on buying interest at Lazada (Y), a significance value of 0.000 was obtained, where this number is smaller or less than (<) 0.05 with a regression coefficient of 0.080, which means it is significant and there is an influence.